Transformational leadership and empowerment as driving factors for employee performance in Star-Rated Hotels in Central Java - Krisnawati Setyaningrum Nugraheni; Dyah Palupiningtyas; Rudi Prasetyo Ardi (Goodwood Publishing, 2025)
Purpose: The aim of this study is to examine how transformational leadership and employee empowerment can improve employee performance in four-star hotels in Central Java. Research Methodology: The research was conducted in four-star hotels in Central Java, involving a survey of 185 hotel employees selected through proportional random sampling. The data was analyzed using Partial Least Square (PLS) to explore the causal relationships between the study variables. Results: The study found that transformational leadership has a strong positive effect on employee empowerment. Additionally, employee empowerment positively influences employee performance. Transformational leadership also directly impacts employee performance in a positive manner. Furthermore, employee empowerment acts as a mediator between transformational leadership and employee performance, with a significant indirect effect. The proposed model exhibited strong predictive ability for both employee empowerment and employee performance. Overall, the relationships examined in the study were consistently positive and significant. Conclusion: The research concludes that both transformational leadership and employee empowerment are crucial for enhancing employee performance in the hotel industry. The interaction between these factors significantly contributes to better performance outcomes Limitations: A limitation of the study is that it focuses solely on four-star hotels in Central Java, which may not be generalizable to other types of hotels or regions. Contribution: This study contributes to the fields of management and hospitality by providing insights into how leadership styles and employee empowerment can work together to boost employee performance. It is valuable for hotel managers, HR professionals, and researchers interested in improving workplace dynamics and performance in the hospitality industry.